Enhanced insulin signaling in density-enhanced phosphatase-1 (DEP-1) knockout mice - Janine Krüger; Sebastian Brachs; Manuela Trappiel; Ulrich Kintscher; Heike Meyborg; Ernst Wellnhofer; Christa Thöne-Reineke; Philipp Stawowy; Arne Östman; Andreas L. Birkenfeld; Frank D. Böhmer; Kai Kappert (Elsevier, 2015)
Objective: Insulin resistance can be triggered by enhanced dephosphorylation of the insulin receptor or downstream components in the insulin signaling cascade through protein tyrosine phosphatases (PTPs). Downregulating density-enhanced phosphatase-1 (DEP-1) resulted in an improved metabolic status in previous analyses. This phenotype was primarily caused by hepatic DEP-1 reduction. Methods: Here we further elucidated the role of DEP-1 in glucose homeostasis by employing a conventional knockout model to explore the specific contribution of DEP-1 in metabolic tissues. Ptprj−/− (DEP-1 deficient) and wild-type C57BL/6 mice were fed a low-fat or high-fat diet. Metabolic phenotyping was combined with analyses of phosphorylation patterns of insulin signaling components. Additionally, experiments with skeletal muscle cells and muscle tissue were performed to assess the role of DEP-1 for glucose uptake. Results: High-fat diet fed-Ptprj−/− mice displayed enhanced insulin sensitivity and improved glucose tolerance. Furthermore, leptin levels and blood pressure were reduced in Ptprj−/− mice. DEP-1 deficiency resulted in increased phosphorylation of components of the insulin signaling cascade in liver, skeletal muscle and adipose tissue after insulin challenge. The beneficial effect on glucose homeostasis in vivo was corroborated by increased glucose uptake in skeletal muscle cells in which DEP-1 was downregulated, and in skeletal muscle of Ptprj−/− mice. Conclusion: Together, these data establish DEP-1 as novel negative regulator of insulin signaling.